Academias de ginástica em Goiânia: lugares de sociabilidade urbana e produção/reprodução do culto ao corpo - Castro, Regina Maria Jordão Cardoso de (2019)
This present study has as its goal to analyse the social and cultural phenomenon which performs as influencer factors in the production/reproduction of a person’s body worship as well as its growth at health clubs in Goiânia-Go with the intention to consider them places of urban sociability.It has a particular purpose:contextualize the production/reproduction of the urban space with the protection of capitalism, the habit of expediture and its influence on the body worship in modernity, characterize the development and expansion of the fitness centers in Brazil and in Goiânia-Go;analyse the market’s approach of gyms inside shopping malls in Goiânia and its effect toward this process;identify and connect the public and private spaces related to physical exercise in Goiânia and analyse the health clubs in this city as privitized places for urban sociability;identify the motivation and goals that lead people to the act of body worship focusing on the construction of identity and sociability in these places.According to the Brazilian Health Club Association(2018), Brazil is still the world leader on the market in the last 10 years and it’s considered to be the largest in Latin America in numbers of gyms(34.509 places), and it’s the second largest in the world, where USA is the number one. In 2017 there were 9,6 million customers in the market, keeping the fourth place at the worldwide ranking of the business but still profting around US$ 2,1 billion which puts it into the twelfth place on the market.The investigative journey orientated by the dialectic method of the slant of marxist geographic critics, linking it and connecting it with a conceptual and reflexive geographic humanist approach and its phenomenology, drawing a qualitative and quantitative scenario once the materiality and subjectivity are inherent to the object of the research, it was mainly used a semi structured interview with different public who build and are part of this business. The spacial and empirical universe of this study started from an investigation about the local range as a reflex of the global range, having as its goal the big health clubs in Goiânia-Go. In a detailed clipping, the study went deeply in four gyms nestled at shopping malls. As main results we can point out that the health clubs can be considered spaces for sociability and leisure that lead people to have social intercourses more often at social networking.By the interviews, it was shown that around 60% of people who work out at the gym also look for socialization, 20% are focused on the results, only 10% follow the rules to achieve the results and the rest use it as a medical prescription.The speech that the health clubs care for a quality service doesn’t match with the real facts : it lacks a good service and satisfaction surveys; there is little professional valorization in order to get more profits; at the same time there’s also a development of the search for studios – small and specialized gyms. As a result, most people think of health clubs as a way of health and quality of life and socialization and this happens specially in colletive classes.However, people even in these places are lonely, needy and in need of estable lovely relationships, revealing contradictions among the speech and every day practice.